JMeter Cookbook. - Erinle, Bayo (Quick answers to common problems, 2014)
This book is great for you if you are a developer, quality assurance engineer, tester, or test manager who is looking to get a firmer grasp of elementary, deep, and advanced testing concepts using Apache JMeter. It's assumed you have access to a computer and an Internet connection. No prior testing or programming experience is required, but would be helpful.